Clinical and genetic characterization of adult‐onset leukoencephalopathy caused by CSF1R mutations. Issue 11 (15th October 2021) - Tsai, Pei‐Chien; Fuh, Jong‐Ling; Yang, Chih‐Chao; Chang, Anna; Lien, Li‐Ming; Wang, Pei‐Ning; Lai, Kuan‐Lin; Tsai, Yu‐Shuen; Lee, Yi‐Chung; Liao, Yi‐Chu
Abstract: Objective: Mutations in the colony‐stimulating factor 1 receptor gene ( CSF1R ) were identified as a cause of adult‐onset inherited leukoencephalopathy. The present study aims at investigating the frequency, clinical characteristics, and functional effects of CSF1R mutations in Taiwanese patients with adult‐onset leukoencephalopathy. Methods: Mutational analysis of CSF1R was performed in 149 unrelated individuals with leukoencephalopathy by a targeted resequencing panel covering the entire coding regions of CSF1R . In vitro analysis of the CSF1‐induced autophosphorylation activities of mutant CSF1R proteins was conducted to assess the pathogenicity of the CSF1R mutations. Results: Among the eight CSF1R variants identified in this study, five mutations led to a loss of CSF1‐induced autophosphorylation of CSF1R proteins. Four mutations (p.K586*, p.G589R, p.R777Q, and p.R782C) located within the tyrosine kinase domain of CSF1R, whereas the p.T79M mutation resided in the immunoglobulin‐like domain. The five patients carrying the CSF1R mutations developed cognitive decline at age 41, 43, 50, 79, and 86 years, respectively. Psychiatric symptoms and behavior changes were observed in four of the five patients. The executive function and processing speed were severely impaired at an early stage, and their cognitive function deteriorated rapidly within 3–4 years. Diffusion‐restricted lesions at the subcortical regions and bilateral corticospinal tracts were found in three patients. Interpretation: CSF1R mutations account for 3.5% (5/149) of the adult‐onset leukoencephalopathy in Taiwan. CSF1R mutations outside the tyrosine kinase domain may also disturb the CSF1R function and lead to the clinical phenotype. Molecular functional validation is important to determine the pathogenicity of novel CSF1R variants.